Pelvic lymph node dissection in high-risk prostate cancer - Luciano Haiquel; Xavier Cathelineau; Rafael Sanchez-Salas; Petr Macek; Fernando Secin (International Brazilian Journal of Urology, 2022)
ABSTRACT Introduction: The therapeutic role of pelvic lymph node dissection (PLND) in prostate cancer (PCa) is unknown due to absence of randomized trials. Objective: to present a critical review on the therapeutic benefits of PLND in high risk localized PCa patients. Materials and Methods: A search of the literature on PLND was performed using PubMed, Cochrane, and Medline database. Articles obtained regarding diagnostic imaging and sentinel lymph node dissection, PLND extension, impact of PLND on survival, PLND in node positive “only” disease and PLND surgical risks were critically reviewed. Results: High-risk PCa commonly develops metastases. In these patients, the possibility of presenting lymph node disease is high. Thus, extended PLND during radical prostatectomy may be recommended in selected patients with localized high-risk PCa for both accurate staging and therapeutic intent. Although recent advances in detecting patients with lymph node involvement (LNI) with novel imaging and sentinel node dissection, extended PLND continues to be the most accurate method to stage lymph node disease, which may be related to the number of nodes removed. However, extended PLND increases surgical time, with potential impact on perioperative complications, hospital length of stay, rehospitalization and healthcare costs. Controversy persists on its therapeutic benefit, particularly in patients with high node burden. Conclusion: The impact of PLND on biochemical recurrence and PCa survival is unclear yet. Selection of patients may benefit from extended PLND but the challenge remains to identify them accurately. Only prospective randomized study would answer the precise role of PLND in high-risk pelvis confined PCa patients.